The Urgency of Expanding the Position and Functions of the Vice President in a Presidential System: A Study on Article 4 of the 1945 Constitution - Prayitno, Herman Bastiaji; Suriaatmadja, Toto Tohir; Darusman, Yoyon M. (Sinergi International Journal of Law, 2024)
This research highlights the role and position of the Vice President within Indonesia's presidential system, which remains ambiguous compared to the clearly defined role and authority of the President. The lack of clarity in the division of duties and the poorly defined role often lead to overlaps or gaps in the responsibilities that the Vice President should fulfill. This can result in uncertainty in decision-making and the implementation of government programs. The presence of a Vice President should ideally add an extra layer of accountability within the government. However, if their role is unclear, the public may find it difficult to assess their performance and to hold them accountable for their actions or decisions. When compared to other countries' constitutions, such as the United States and the Philippines, the role of the Vice President is more defined, but the role of the Indonesian Vice President appears to be more dependent on the President's policies. In the 1945 Constitution of Indonesia, the role of the Vice President is only broadly outlined in Article 4 paragraph (2) and Article 8. This ambiguity causes the Vice President's authority to depend on the President's policies. This research utilizes legal regulation, conceptual, and comparative approaches to understand the Vice President's position and powers. The research findings indicate that the Vice President's role is intended to assist the President and has a primary role in assuming the President's position in accordance with Article 8 of the 1945 Constitution. However, the Vice President's role does not have absolute authority as their power depends on the President's policies and preferences. This creates a complex dynamic between the President and the Vice President, with the Vice President's authority merely shadowing the President's power. Upon examining Article 4 of the 1945 Constitution, the Vice President's role should emulate that of the Vice President of the United States. According to this provision, the Vice President, with support from the Ministers, has the authority to declare the President's incapacity to exercise power and presidential duties, and conversely, the President can make statements contrary to the Vice President's statements, complementing each other.